Peran Mahkamah Konstitusi dalam Mengawal Prinsip Checks and Balances Terhadap Dewan Perwakilan Daerah di Indonesia - Ivana Eka Kusuma Wardani (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2019)
This article is intended to answer the role of the Constitutional Court in overseeing checks and balances function of Regional Representative Council. This article is a normative study using normative approach. This article concludes that in performing its role, the Constitutional Court has influential authority for state institutions to support the implementation of structured constitutional system using checks and balances principles. Through the judicial review mechanism, the Constitutional Court functions as an interpreter of the 1945 Constitution. Decision of the Constitutional Court Number 30 / PUU-XVII / 2018 proves the role of the Constitutional Court in maintaining the implementation of checks and balances principles in Indonesia